Non-traumatic subarachnoid haemorhage: clinical onset symptoms as predictors for patients` clinical outcome - Цьома, Євгенія Іванівна; Смоланка, Володимир Іванович; Чомоляк, Юрій Юрійович; Студеняк, Тарас Олександрович (ScienceRise: Medical Science, 2017)
Aim. In this article, we tried to find out whether any of SAH clinical symptoms can be both short-term and long-term predictors for patients. Materials. 144 SAH / unruptured aneurysm patients, treated at Uzhgorod Regional Center of neurology and neurosurgery during 4 years, were examined. The patients were examined on standardized scales (WFNS, Hunt-Hess, GCS), neurovisual and other clinical criteria. The early clinical outcome was determined by GlasgowOutcomeScale. Results and discussion. Considering the given clinical data, we can identify several predictors of a positive early outcome after aneurismal subarachnoid hemorrhage (i.e. 4 – 5 Glasgow Outcome Scale points): - High level of consciousness, according to the GSC scale, at the moment of hospitalization; - Hunt-Hess / WFNS I-II. At the same time, low indicators of these scales in the disease onset are associated with a worse early outcome (1 – 3 Glasgow Outcome Scale points). The young age is SAH risk factor, but it’s not the unambiguous feature for the disease prediction. Also, a hypertension in anamnesis is one of the worse prediction indexes. Conclusion. A correlation between epileptic seizures in SAH onset and higher risk of rebleeding was found out. Therefore, this clinical symptom can be a negative outcome predictor and requires more thorough attention and study. We believe that even patients with good neurological recovery and the relative / complete independence after SAH in future can suffer from anxiety, depression, post-traumatic stress disorder and cognitive impairment, affecting quality of their lives. It should be considered in the long term – with cognitive function study and the use of quality of life scale in routine practice after SAH